Housebuilding development in Malaysia / Kamaruddin Bujang - Bujang, Kamaruddin (1981)
The increasing need of housing in Malaysia is now hotly felt "by the people. Despite of the price they are passionately hunting for one. Among the reasons for such rush come from the following: i. Immigrants especially the young generation hunting for job in urbanised towns such as Kuala Lumpur and Johore Bahru. ii. The approximity of working areas is the first priority, thus, the demand for this advantage is very high. iii. The desire of house brokers. The great demand causes an appreciation of housing sale price, thus, encourage a section of people to buy as an asset(s) in future. All these factors cause an unproportion situation in housing demand and create price bidding which give rise to the reason of price hike. This great demand encourages housing speculation around the country. The condition is now getting worse as the population of immigrantion has grew to an alarming stage